Eksplorasi Etnomatematika pada Kain Tenun di Sanggar Seni Ori Angu Waingapu - Talo, Yohana Anggreni; Cordia, Grassiana Misseri; Wadu, Welhem Mine; Lede, Yulius Keremata; Bili, Fransiskus Ghunu; Tana, Wilibrondus Pangga (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to determine the mathematical elements contained in woven fabrics at the Ori Angu Waingapu Art Studio. This type of research is descriptive qualitative. The subjects in the study were two cloth traders at the Ori Angu Waingapu Art Studio and the object of the research was Ethnomathematics in Woven Fabrics at the Ori Angu Art Studio. The instruments used in this study were observation sheets, interview sheets, field notes and documentation. The research data analyzed were qualitative research data carried out through three simultaneous activity flows, namely data reduction, data presentation, and conclusion drawing. The results of the study were to find mathematical elements in algebraic form, namely the number of images contained in woven fabrics and more using the formula for the area of a rectangle (P) times the width (L) to calculate a collection of images arranged regularly on woven fabrics. So this discovery got two things, namely using algebraic formulas and rectangular area formulas.